NUMERICAL INVESTIGATION OF THE SINGLE PHASE FORCED CONVECTION HEAT TRANSFER CHARACTERISTICS OF NANOFLUID FLOWING IN CIRCULAR AND NONCIRCULAR TUBES - Kayaci, Nurullah; Malazi, Mahdi Tabatabaei; Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2016)
Thermal conductivity is an important parameter that expresses the heat transfer performance of a heat transfer fluid. Due to their low thermal conductivity, conventional heat transfer fluids (e.g. water, oil, ethylene glycol mixtures) restrict the enhancement of performance and compactness in heat exchangers used in the electronic, automotive, and aerospace industries.Nanofluids are functional liquid suspensions including particles that are smaller than 100 nm. These smaller sized particles allowed forming uniform and stable suspensions. The most well-known nanoparticles are Al2O3, CuO, TiO2, each of which is used, together with the base fluids of water and ethylene glycol, in the experimental work of many researchers. Across the range of particle sizes and types of base fluids, the enhancement of thermal conductivity has been achieved under all experimental conditions with these nanoparticles. The nanofluids provide higher heat transfer enhancement than existing techniques. With some improved properties, they have extensive potential application for concentrating heat transfer performance in a variety of systems. Forced convection flows of nanofluids containing of water with TiO2 and AI(2)O(3) nanoparticles in circular and noncircular tubes with constant wall temperature are investigated numerically in this paper. A single-phase numerical model having three-dimensional equations is solved with either constant heat flux or temperature dependent properties to determine the hydrodynamics and thermal behaviors of the nanofluid flow by means of a CFD program for the water flow in circular and noncircular tubes. An intensive literature review on the determination of the physical properties (k, mu, rho, Cp) of nanofluids is given in the paper. The software package ANSYS Fluent was employed in the numerical study. Investigated tubes were plotted in the SolidWorks program and were imported to ANSYS Geometry. After the investigated tubes were imported to ANSYS Geometry, they were forwarded for meshing in the ANSYS Meshing program. The mesh influences the accuracy, convergence, and speed of the solution. Furthermore, the time required to create a mesh model often represents a significant portion of the time required to acquire results from the solutions; this means that the better and more automated the meshing tools, the better the solution.The numerical model is validated by means of a CFD program to compare the experimental smooth tube data as a case study and it is also solved in the CFD program for noncircular tubes as a simulation study. Velocity, temperature and pressure distributions are shown in the paper. Morever, the values of experimental and numerical are compared with each other in terms of convective heat transfer coefficients and pressure drops. Besides this, the effects of the presence of nanofluids and noncircular tubes on the heat transfer characteristics are investigated in detail.
Keywords: THERMAL-CONDUCTIVITY; PRESSURE-DROP; Engineering